Regulation of Haemoglobin Synthesis - Neuwirt, J; Poňka, P (Martinus Nijhoff, 1977)
Haemoglobin is one of the most important molecules in the animal kingdom. Its function is to carry oxygen to tissues. In lower invertebrates the blood pigment is present in the haemolymph and is not bound in cells. Later in the course of phylo genesis haemoglobin remains associated with cells which produce it and in this form it reaches the peripheral circulation. In higher organisms the haemoglobin production is thus determined by two main factors: haemoglobin synthesis in erythroid cells and the formation of these erythroid cells which depends on cell proliferation in haematopoietic organs. Human haemoglobin is made up of two chains which combine from four different polypeptide chains formed in varying ratios in different periods of the life cycle. During the life span of humans the following haemoglobins are formed: embryonic haemoglobins Gower 1 and 2, foetal haemoglobin F and two adult haemoglobins A and A . E-and IX-chains are part of the embryonic haemoglobins Gower 1 (E4) and 2 Gower 2 (1X2E2). These haemoglobins predominate in embryos during the second month of pregnancy and at the end of the first trimester they are completely re placed by foetal haemoglobin F (~Y2). Adult haemoglobin A consists of two IX and two ~-chains and is the main component of red cells in adults. A relatively small component of red cells accounting for less than 2 % of the total haemo globin, is haemoglobin A2 (1X0).